Diseño de máquina para posicionar cilindros de gas después de la prueba hidrostática para la empresa Linde Colombia S.A. (2017)
The present work proposes a machine design that enables the drainage of gas cylinders employed by the company Linde Colombia SA. It began with the evaluation of the current drainage process of gas cylinders, through which it was determined that once the hydrostatic test is performed, the cylinders end up completely full of water that must be properly drained.